RESPON JANGKA PENDEK PASAR SAHAM INDONESIA TERHADAP PERISTIWA POLITIK - BAMBANG SUTRISNO (SMART Management Journal, 2021)
This study is entitled the short-term response of the Indonesian stock market to political events. This study aims to analyze the market reaction to the holding of the presidential election of the Republic of Indonesia which took place in 2019. The researcher uses the literature study method, which is used to observe the information content of a political event that occurs. This study is also intended to examine the difference in the effect of presidential election events on companies under government control and private companies. The research object used is 437 companies listed on the Indonesia Stock Exchange. The results of the research show that abnormal returns are negative the day before the election, then a reversal occurs the day after the election, where the abnormal return value increases and becomes positive, this shows that investors are confident that the presidential election is going well. The results of this study also show that companies under government control are more likely to feel the effects of the presidential election event than private companies.